AN ANALYSIS OF SPEECH FUNCTIONS ON THE BANKING AND DAILY NEED BILLBOARD TEXTS - Muhammad Hasyimsyah Batubara (Sanata Dharma University, 2020)
This research aims at describing speech functions in banking and daily need billboard texts. The objectives are to describe the category and to derive dominantly used and explain the factors of the phenomenon of speech functions. The research method used descriptive qualitative. The data collecting procedures include applying documentary techniques from banking and daily need billboard texts (headline, subhead, slogan, and images) in public places around the city center of Medan. The findings describe the three speech functions available used banking and daily need billboard texts, the statement constitutes 15, offer 10, and command 8 from 33 billboard texts. The statement genre is used as the dominant one as it is suitable with the pattern of commercial billboard texts, where the viewer assumed only briefly saw the display of text and images of the billboard with a duration of 5-7 seconds when they were driving. There is a phenomenon, especially in the banking domain, which offers the most dominant is one used. Thus, authoritative and straightforward information in the speech function of functional grammar and the language used must be efficient, effective, and able to hypnotize readers, so that results in decisive action on the item advertised.